# 6(n-5)=-18+4n

## Simple and best practice solution for 6(n-5)=-18+4n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6(n-5)=-18+4n equation:

Simplifying
6(n + -5) = -18 + 4n
Reorder the terms:
6(-5 + n) = -18 + 4n
(-5 * 6 + n * 6) = -18 + 4n
(-30 + 6n) = -18 + 4n
Solving
-30 + 6n = -18 + 4n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '-4n' to each side of the equation.
-30 + 6n + -4n = -18 + 4n + -4n
Combine like terms: 6n + -4n = 2n
-30 + 2n = -18 + 4n + -4n
Combine like terms: 4n + -4n = 0
-30 + 2n = -18 + 0
-30 + 2n = -18
Add '30' to each side of the equation.
-30 + 30 + 2n = -18 + 30
Combine like terms: -30 + 30 = 0
0 + 2n = -18 + 30
2n = -18 + 30
Combine like terms: -18 + 30 = 12
2n = 12
Divide each side by '2'.
n = 6
Simplifying
n = 6`